Pseudocapacitance induced candle soot derived carbon for high energy density electrochemical supercapacitors: Non-aqueous approach. (February 2020) - Potphode, Darshna; Sharma, Chandra Shekhar
Highlights: Simple synthesis of high-performance interconnected carbon sphericals for energy storage. Candle soot: pure and cheapest source of carbon proven as potent electrode material. Capacitance of 64 and 88.4 f g −1 achieved in organic and ionic liquid electrolytes respectively. Capacitance retention was attained up to 82–85% after 5000 charge-discharge cycles. Candle soot based supercapacitor achieved highest specific energy 28 Wh kg −1 and specific power 15 kW kg −1 . Abstract: The commercialization aspect in electric double layer capacitors is highly dependent on source of carbon, its purity, and the specific capacitance with unique deliverable for proficient charge storage. Here, we report synthesis of interconnected mesoporous spherical carbon by direct flame synthesis using candle wax for symmetric supercapacitors with the non-aqueous approach. The heat treated candle soot (CST) at 450 °C results in a high purity carbon with the improved surface area of 608 m 2 g −1 also the majority of pores in the range of 1–10 nm, which is ideal for charge storage in supercapacitors. The highest capacitance of 64 and 88.2 F g −1 at 0.1 A g −1 was obtained for 1 M TEABF4 in acetonitrile and EMIM BF4, respectively. A stability up to 82–85% can be achieved for 5, 000 charge-discharge cycles. CST as a potent electrode material successfully delivered highest specific energy of 14 and 28 Wh kg −1 and specific power of 12.5 and 15 kW kg −1 in 1 M TEABF4 in ACN and EMIM BF4 electrolytes, respectively. Graphical abstract: A facile approach to achieve high energy density supercapacitors with highly ordered mesoporous nano carbon. Coin cell assembly for candle soot carbon-based non-aqueous supercapacitor further excels in terms of electrochemical performance, more precisely with electrochemical charge storage, energy density, and stability. An approach transforms waste material to advanced electrodes for productive energy storage and can be implemented in future energy storage systems. Image, graphical abstract